Leuconostoc citreum MB1 as biocontrol agent of Listeria monocytogenes in milk - Pujato, Silvina (2013)
Cell-free supernatant from Leuconostoc citreum MB1 revealed specific antilisterial activity. Preliminary studies demonstrated the proteinaceous, heat-stable, bacteriocin-like trait of the antimicrobial components present in the supernatant. Determination of the genes encoding bacteriocins by PCR and DNA sequencing led to amplification products highly homologous with leucocin A (found in diverse Leuconostoc species) and UviB (found in Leuc. citreum KM20) sequences. Additionally, antimicrobial activity of cell-free supernatant from Leuc. citreum MB1 was revealed by an inhibition halo of the SDS-PAGE gel subjected to a direct detection using Listeria monocytogenes as indicator strain. Different assays were carried out to assess the capacity of Leuc. citreum MB1 to control List. monocytogenes growth: (i) inactivation kinetics of the pathogen by antilisterial compounds present in concentrated cell-free supernatant from Leuc. citreum MB1, (ii) evaluation of optimal Leuc. citreum MB1 initial concentration to obtain maximum List. monocytogenes ATCC 15313 inhibition, and (iii) biocontrol of List. monocytogenes ATCC 15313 with Leuc. citreum MB1 during growth in milk at refrigeration temperature. According to our results, it is unquestionable that at least one bacteriocin is active in Leuc. citreum MB1, since important antilisterial activity was verified either in its cell-free supernatant or in co-culture experiments. Co-culture tests showed that*107 CFU/ml Leuc. citreum MB1 was the optimal initial concentration to obtain maximum pathogen inhibition. Moreover, Leuc. citreum MB1 was able to delay List. monocytogenes growth at refrigerated temperature.